The Kaurs of 1984: the untold, unheard stories of Sikh women - Wazir, Sanam Sutirath (HarperCollins Publshers India, 2024)
More than three decades after Operation Blue Star of June 1984 and the anti-Sikh violence later that year, a young man is given the task of researching the violence. What he finds devastates him. Among the many oral testimonies, one crucial constituency has remained silent. Hundreds of Sikh women witnessed hell coming to life that year. These included women who were stranded inside the Golden Temple, who stood by their militant men, and those who were, at one time in their lives, militants themselves. They are rape survivors. They are among the murdered. They are the forgotten. Sanam Sutirath Wazir's research has taken him across north India to meet the women who lived to tell the tale, many of whom are still fighting invisible battles for justice. Based on interviews and extensive historical research, in The Kaurs of 1984, Wazir weaves together scattered stories of grief, betrayal and loss that finally brings Sikh women out of the shadows of contemporary Indian history